PENGELOLAAN LABORATORIUM BIOLOGI UNTUK MENUNJANG KINERJA PENGGUNA DAN PENGELOLA LABORATORIUM BIOLOGI SMA NEGERI 2 WONOGIRI - Anggraeni, Aprilianingtyas; Retnoningsih, Amin; Herlina, Lina (Journal of Biology Education, 2013)
This research is an action research. The research objective is to improve the management biology laboratory to support user performance and laboratory manager. Research conducted at SMAN 2 Wonogiri Biology laboratory in the second semester of academic year 2011/2012. Laboratory was used for practical activities, but has not been fully utilized because optimal management has not done. Research activity consists of four phases: planning, action, observation and reflection. Indicator of success is the performance of the users and managers of minimal laboratory showed that both criteria are in the range 50-75%. Performance criteria for teachers to get very good but there are still aspects of performance that has not reached 100% performance in preparing the lab for students. Performance of students gained on average very good, but the performance in carrying out practical activities and communicate the results practice obtain results less than 75%. Laboratory manager performance is very good but there are still aspects of performance that has not reached 100% the administrative performance. Improved management of biological laboratories capable of supporting users and managing the performance of SMAN 2Wonogiri Biology laboratory.Â Penelitian ini merupakan penelitian tindakan atau action research. Tujuan penelitian adalah untuk memperbaiki pengelolaan laboratorium Biologi guna menunjang kinerja pengguna dan pengelola laboratorium. Penelitian dilaksanakan di laboratorium Biologi SMA Negeri 2 Wonogiri pada semester genap tahun ajaran 2011/2012. Laboratorium sudah digunakan untuk kegiatan praktikum,tetapi belum dimanfaatkan secara maksimal karena belum dilakukan pengelolaan yang optimal.Kegiatan penelitian terdiri atas empat tahap yaitu tahap perencanaan, tindakan, pengamatan dan refleksi. Indikator keberhasilan adalah kinerja pengguna dan pengelola laboratorium minimal menunjukkan kriteria baik yaitu berada pada rentang 50-75%. Kinerja guru memperoleh kriteria sangat baik tetapi masih terdapat aspek kinerja yang belum mencapai 100% yaitu kinerja dalam menyiapkan praktikum untuk siswa. Kinerja siswa memperoleh rata-rata sangat baik, tetapi kinerja dalam melaksanakan kegiatan praktikum dan mengkomunikasikan hasil praktikum memperoleh hasil kurang dari 75%. Kinerja pengelola laboratorium sudah sangat baik tetapi masih terdapat aspek kinerja yang belum mencapai 100% yaitu kinerja administratif. Perbaikan pengelolaan laboratorium biologi mampu menunjang kinerja pengguna dan pengelola laboratorium BiologiSMA Negeri 2 Wonogiri.